Energy Flexibility and towards Resilience in New and Old Residential Houses in Cold Climates: A Techno-Economic Analysis - Hassam ur Rehman; Ala Hasan (Energies, 2023)
One of the main sectors that contribute to climate change is the buildings sector. While nearly zero-energy buildings are becoming a new norm in many countries in the world, research is advancing towards energy flexibility and resilience to reach energy efficiency and sustainability goals. Combining the energy flexibility and energy resilience concept is rare. In this article, we aim to investigate the effect of energy efficiency in a new single-family building on the energy flexibility potential and resilience characteristics and compare these with those for an old building in the cold climate of Finland. These two objectives are dependent on the buildings’ respective thermal mass. The heat demands of the two buildings are compared. Their technical and economic performance are calculated to compare their flexibility and resilience characteristics. Dynamic simulation software is used to model the buildings. The results show that the old building has better flexibility and higher energy cost savings when including the energy conservation activation strategy. In the old building, savings can be around EUR 400 and flexibility factor can be around 24–52% depending on the activation duration and strategy. The new building, due to higher efficiency, may not provide higher energy cost savings, and the energy conservation activation strategy is better. In the new building, savings can be around EUR 70 and the flexibility factor reaches around 7–14% depending on the activation duration and strategy. The shifting efficiency of the new house is better compared to that of the old house due to its higher storage capacity. For energy resilience, the new building is shown to be better during power outages. The new building can be habitable for 17 h, while the old building can provide the same conditions for 3 h only. Therefore, it is essential to consider both energy flexibility and resilience as this can impact performance during the energy crisis.